STANDARISASI KURIKULUM PENDIDIKAN BAHASA ARAB DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI - Muhbib Abdul Wahab (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This study aimed at assessing and analyzing the bases of the standardization of KKNI-based curricular development of Arabic language education. The method used in this study was a qualitative method based on text analysis. Therefore, the analysis that was used to read and interpret qualitative data is content and system analyses. This study concluded that the standardization of Arabic language education curriculum should ideally be developed integratively, holistically and humanistically. Arabic language education curriculum development in the future must be based on philosophical, socio-cultural and linguistic theories, educational, technological and management educational bases; so that the Arabic language learning system developed could run more effectively. The standardization of KKNI and SNPT-based Arabic language curriculum should be developed as a multi-integrated system combined with four language skills plus study skills, theories of Arabic language education that are relevant to the development goals of the department, and the provision of real experience (e. g. live and interact with the Arab community) in a certain period of time in one of the Arab countries, while conducting a research and writing a scientific writing.DOI : 10.15408/a.v3i1.3187